DAMPAK MODAL SOSIAL DALAM PENGELOLAAN IRIGASI TERHADAP KESEJAHTERAAN PETANI DI KABUPATEN SUKOHARJO JAWA TENGAH - Rohmani, Sri Asih (Informatika Pertanian, 2015)
Regulation in the utilization of irrigation as Common Pool Resources-CPRs is really needed to overcome water limitation. Conducive conditions for the irrigation management on overall hydrological unit will be strengthened by the presence of social capital. Social capital plays a role in the mechanism of collective action formation on the management of CPRs whose existence depends on the people’s social and cultural environment. Trust will reduce transaction costs and facilitate the formation of social cooperation (network). Establishment of social bonds and norms in the groups become an effective instrument for resource sustainability. The study aims to analyze the role of social capital in the irrigation management and its impact to the farmers welfare. The study was conducted from April to August 2014 In Sukoharjo,with 320 respondents who represent the hydrological diversity unit of 12 districts in Sukoharjo. Using the two levels regression analysis, namely at the micro-level (farmers household) and meso-level (community) to see the effect of different variables: social capital of farmer households (Iik), social capital of community (Mk), area access (R), access and availability of water resources (Hdr), external environment (E), the collective action of irrigation management (TK), farmers satisfaction (Stfy), highly significant effect to the farmer household welfare (Sik) and community level (wk). Social capital of community, area access, access and availability of water resources have a significant effect to the society welfare (Wk). Therefore, the implementation of irrigation management should provide space for the establishment of social capital accompanied by policies harmonization between the formal regulations and informal rules in the form of the value system and culture that flourished in the society life.